The leadership competencies of the heads of the national Olympic sports federations from the point of view of their members (Journal of the College of Basic Education, 2024)
The current research aims:- Building a measure of the leadership competencies of the heads of the Olympic national sports federations from the point of view of its members.- Identifying the level of leadership competencies of the heads of the Olympic national sports federations from the point of view of its members.The researchers used the descriptive approach due to its suitability to the nature of the current research, and the research sample included members of the Olympic national sports federations, and the researcher used the questionnaire as a tool for data collection, and the researchers used the spss 25 statistical bag to analyze the data statistically and reached a set of conclusions, including:- The researcher reached to build a scale of leadership competencies prepared by the researcher, suitable for measuring the level of heads of the Iraqi Olympic federations in the variables of leadership competencies according to (5) axes distributed over them (48) paragraphs.- The heads of the Iraqi Olympic federations have a (good) level in the merit of planning from the point of view of the federation members according to the response levels of the research sample, and this axis comes in the first place among the other axes of the scale.